A Selective and Sustainable Sulfoxidation Method Catalyzed by Reusable Manganese (III) Schiff Base Complexes - Rezaeifard, Abdolreza; Jafarpour, Maasoumeh; Haddad, Reza; Farrokhi, Alireza (Current Catalysis, 2015)
A novel environmentally benign oxidation method for practical and highly selective production of various sulfoxides using n-Bu4NHSO5 catalyzed by simple tetradentate Schiff base Mn(III)-complexes in ethanol under mild conditions has been developed. The salen catalyst proved to be reusable for at least three times and the oxidant’s by-product (n- Bu4NHSO4) could also be recycled. The efficiency of the catalytic system was influenced by the nature of ligands so the best yields were achieved in the presence of Mn(Salphen)Cl as catalyst.
Keywords: Mn-complexes